Interrelated Dynamics of Health and Poverty in Australia - Buddelmeyer, H; Cai, L (My University, 2009)
Using the Household, Income and Labour Dynamics in Australia (HILDA) Survey, this study examines the joint dynamics of health and poverty in Australian families. Taking advantage of panel data, the modelling approach used in this study allows a better estimation of the causal relationship between health and poverty. The results indicate that the causality between health and poverty runs both ways and the relationship is confounded by unobserved heterogeneity. In particular, it is found that families headed by a person in ill-health are more likely to be in poverty compared with families headed by a person with good health. On the other hand, a family head whose family is in poverty in the current year is more likely to be in ill-health in the next year compared with a family head whose family is not in poverty. In addition, there is evidence that health and poverty are affected by correlated unobservables, causing health to be endogenous to poverty even in the absence of a reverse effect from poverty on health. Consequently, treating health as exogenous in a poverty equation would produce biased estimates.
IZA Discussion Paper
Keywords: Finance; Finance -- Poverty and disadvantage; Health; Health and wellbeing; Income, wealth and finances; Health; Finance; Poverty and disadvantage; Income, wealth and finance; Health and wellbeing